Penerapan Anggaran Berbasis Kinerja Pada Dinas Kesehatan Kota Bandung - Supyani Supyani; Khaerul Umam (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2020)
This journal discusses the application of performance-based budgeting at the Bandung City Health Office. The budgeting process at government agencies currently uses a performance-based budgeting approach. This study aims to determine the implementation of performance-based budgeting at the Bandung City Health Office by looking at inhibiting factors in the implementation of performance-based budgeting, as well as knowing the steps that have been taken by the Bandung City Health Office in overcoming budgeting problems. The results of this study indicate the application of performance-based budgeting at the Bandung City Health Office has been carried out in a clear, relevant, economic, adequate and monitorable manner. However, the implementation is still not optimal, this is due to the lack of available budget, the existence of collaborative tasks with other agencies and the lack of information support provided by health workers. Barriers come from internally such as lack of available budget and come from externals such as changes in the economic and social environment that cause changes in prices and changes in disease patterns.